Male infertility as a late side effect of oncological treatment of Hodgkin lymphoma in childhood and adolescents and the possible prevention - Prusak, Michelle; Brylka, Katarzyna; Derwich, Katarzyna (Frontiers in Oncology, 2025)
As the cohort of childhood and adolescent survivors of Hodgkin lymphoma (HL) continues to grow, the possibility of preserving long-term fertility has only amplified in the last decade. With the increasing success of pediatric cancer treatment outcomes, survivors now have the hope of having children of their own. This article critically reviews the relevant methods of gonadal function assessments and treatment therapies. It focuses on the most up-to-date methods of fertility preservation for male Hodgkin lymphoma survivors. Cure rates for HL remain among the best for pediatric cancers, with an overall success of 90-95% attributed to modern treatment. Although efforts to prevent gonadal toxicity continue to be of the utmost importance, ramifications of treatment have prevailed and sperm cryopreservation remains the gold standard method of fertility preservation. Pediatric physicians experience challenges in oncofertility that hinder the provision of high-quality fertility preservation care and patients endure a multitude of physical and psychological consequences that can exacerbate long-term fertility outcomes. Accordingly, fertility maintenance and protection must be considered extremely significant in all young male patients regardless of age, for maximal fertility quality and long-term potential for reproduction. Given the advancements in modern medicine, it is crucial to mitigate the long-term effects of treatments and prioritize fertility preservation options for young males to promote their reproductive autonomy.